Carbon dot based nucleus targeted fluorescence imaging and detection of nuclear hydrogen peroxide in living cells. Issue 1 (10th November 2021) - Phukan, Kabyashree; Sarma, Ritwick Ranjan; Dash, Somarani; Devi, Rajlakshmi; Chowdhury, Devasish
Abstract : Detection of exogenous and endogenous H2 O2 using boron doped p -phenylenediamine based carbon quantum dots (B-PPD CDs) in RAW 264.7 cells. Abstract : Investigation of the intracellular generation of H2 O2, one of the most important reactive oxygen species (ROS), is crucial for preventing various diseases since it is closely linked with different physiological and complex cell signaling pathways. Despite the development of various fluorescent probes, the majority of the fluorescent probes cannot move across the nuclear membrane. However, detection of the nuclear level of H2 O2 is very important since it can directly cause oxidative DNA damage which ultimately leads to various diseases. Therefore, in this study, p -phenylenediamine based carbon quantum dots (B-PPD CDs) have been synthesized and integrated with 4-formylbenzeneboronic acid as a doping agent for the detection of H2 O2 . The detection mechanism showed that, upon exposure to H2 O2, the fluorescence of the B-PPD CDs was immediately quenched. Further investigation has been done in the in vitro RAW 264.7 cell line by both exogenous and endogenous exposure of H2 O2 to demonstrate the feasibility of the method. It is shown successfully that the exogenous presence and endogenous generation of H2 O2 in RAW 264.7 cells can be detected using B-PPD CDs. The limit of detection (LOD) was determined to be 0.242 μM. The development of such imaging probes using carbon quantum dots will lead to live-cell imaging as well as ROS detection.